Synthesis and characterization of ZnO NRs with spray coated GO for enhanced photocatalytic activity. Issue 13 (1st July 2022) - Mohd Raub, Aini Ayuni; Yunas, Jumril; Mohamed, Mohd Ambri; Bais, Badariah; Hamzah, Azrul Azlan; Ridwan, Jaenudin; Kazmi, Jamal; Hassan, Muhamad Azuddin
Abstract: Zinc oxide nanorods, ZnO NRs, were synthesized on a clean glass and coated with graphene oxide (GO) using spray coating method to enhance the photocatalytic activity in wastewater treatment. The ZnO NRs were synthesized using the solution process synthesis that was optimized using Taguchi method. Several synthesis parameters have been optimized and studied to determine the best synthesis parameter to grow ZnO NRs for the photodegradation of organic contaminants. Field emission scanning electron microscopy (FESEM) with EDX, X-ray diffraction (XRD), Raman, ultraviolet visible near-infrared (UV-VIS-NIR), and photoluminescence (PL) spectroscopies were used to investigate the structural and optical properties of the produced nanorods. FESEM images revealed the vertical growth of ZnO NRs as well as layers of GO covering the ZnO NRs' top surface. The Raman study demonstrates the combination peak of GO and ZnO, hence proving the GO layer's successful coating. After the GO coating, decrease in the bandgap of the synthesized photocatalyst was detected by PL and UV–Vis absorption measurements. Under UVC exposure with treatment time of 6 h, the degradation of MB with ZnO NRs/GO photocatalyst reached a degradation percentage of 97.86%, which is greater than the degradation percentage achieved using pristine ZnO NRs, which is 93.28%. The results validated that the coating of GO enhances the photocatalytic activity of the host material, ZnO NRs.